Conflicts between Students Living on-Campus Dormitories: The Case of Dormitories at Eastern Mediterranean University Campus - Jobbehdar Nourafkan, Nadia; Jumah , Balsam; Asif, Rabia; DEHGHANMONGABADI, Abolfazl (SEISENSE Journal of Management, 2020)
Purpose- In the current century, the number of students who travel abroad to study at international higher education institutions universally has increased. Accordingly, a considerable number of young generations from different countries are coming together, and most of them prefer to live at the university’s dormitories. The main aim of this research has identified and examined the impacts of roommate conflicts, on the lifestyle and academic success of students living in dormitories. Design/Methodology- The study area of this research is the dormitories located inside the Campus of Eastern Mediterranean University in Famagusta, Northern Cyprus. Data was collected by utilizing both qualitative and quantitative methods. Findings- The results showed that conflicts amidst roommates negatively influenced their lifestyle and academic success. Although it is impossible to solve problems and conflicts at all, however, it is possible to minimize and control them. Moreover, management styles and approaches play a fundamental role in reducing or increasing negative impacts. Practical Implications- Several suggestions mentioned for managers to minimize problems, like price reduction, qualified staff employment, evaluation of dormitories, rewriting the rules against alcohol consumption and making noise, and etc.